Development of Approaches and Metrics to Measure the Impact and Improve the Clinical Outcomes of Patients With Frailty in the Era of COVID-19. The COMETA Italian Protocol - Silvestris, Nicola; Belleudi, Valeria; Addis, Antonio; Pimpinelli, Fulvia; Morrone, Aldo; Sciacchitano, Salvatore; Mancini, Rita; Garrisi, Vito Michele; Costantini, Massimo; Ciliberto, Gennaro; Frisardi, Vincenza; Piaggio, Giulia (Frontiers in Oncology, 2022)
The outbreak of the coronavirus 2 disease 2019 (COVID-19) puts an enormous burden on health care systems worldwide. This may worsen outcomes in patients with severe chronic diseases such as cancer, autoimmune diseases, and immune deficiencies worsening. In this critical situation, only a few available data exist, which do not allow us to provide practical guides for the treatment of oncological or immunocompromised patients. Therefore, a further step forward is needed, addressing the specific needs and demands of frail patients in the pandemic era. Here we aim to present a protocol of a study approved by an ethical committee named “CO.M.E.TA”. CO.M.E.TA protocol is a network project involving six Italian institutions whose goals are: i) to measure and compare the impact of the pandemic on the access of cancer and immunocompromised patients to therapies in three Italian regions; ii) to assess how reorganizational measures put in place in these different institutions have impacted on specific metrics of performance; iii) to establish a COVID-19 Biobank of biological samples from SARS-Cov-2 infected patients to be used to study immunological alterations in patients with immune frailty.